Factors Influencing Recycling Behavior among Generation Y Population: A Study in Nilai, Malaysia - Lin, Jing (2014)
With the development of city, the population in the cities also increases. Huge amount of garbage is generated daily in the city, causing great damage to the environment. In order to protect the environment better, to recovery and utilization of municipal waste is essential. But if there is no support and participation of the public, waste recycling is very difficult. As a developing country, Malaysia faces problems of waste generation. Management of municipal solid waste becomes a major environmental problem because of rapid population growth, inadequate expertise and infrastructure. In order to achieve sustainable waste management, recycling is one of the main key factors. Therefore, the objective of this study is to find out the factors influencing recycling behavior among Generation Y in Nilai, Malaysia. Generation Y are people who were born between 1977 and 1994. In this study, quantitative method will be used. 200 questionnaires will be distributed to the respondents in public areas. The respondents are individuals from Generation Y who lived or studied in Nilai, Malaysia. The data will be analyzed using SPSS software version 2.0; reliability testing and factor analysis would be used to determine the reliability and validity of the questions before analysis of the date.